2022
DOI: 10.1021/acs.iecr.2c02243
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Catalytic Oxidation of Hydrogen Chloride to Chlorine from Thermodynamics and Reaction Kinetics

Abstract: The vast emission of hydrogen chloride (HCl) in the chlorination industry has raised great interest in producing chlorine (Cl 2 ) directly from HCl. In this work, thermodynamic analysis and kinetic studies were carried out to understand the engineering of the catalytic oxidation of HCl to Cl 2 . Thermodynamic calculation indicates that the equilibrium conversion of HCl decreases with an increase in the reaction temperature and feed molar ratio n(HCl)/n(O 2 ), and the equal molar HCl/O 2 feed results in a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…And both high and low temperatures were not conducive to the synthesis of citral. It has been shown that the reaction can be carried out more smoothly by changing the temperature and molar ratio of the system, and increasing the pressure was beneficial to both kinetics and thermodynamics. , Zhou et al demonstrated that excessive temperature was not favorable for the D–A reaction of 2-(1-alkynyl)-2-alken-1-ones and enals, and an appropriate reaction temperature was crucial for the D–A reaction. At a reaction temperature of 60 °C with toluene as the solvent, the final product yield can reach 62%.…”
Section: Introductionmentioning
confidence: 99%
“…And both high and low temperatures were not conducive to the synthesis of citral. It has been shown that the reaction can be carried out more smoothly by changing the temperature and molar ratio of the system, and increasing the pressure was beneficial to both kinetics and thermodynamics. , Zhou et al demonstrated that excessive temperature was not favorable for the D–A reaction of 2-(1-alkynyl)-2-alken-1-ones and enals, and an appropriate reaction temperature was crucial for the D–A reaction. At a reaction temperature of 60 °C with toluene as the solvent, the final product yield can reach 62%.…”
Section: Introductionmentioning
confidence: 99%
“…Almost 50% of chemical processes involve chlorine, while 50% of the used chlorine is discharged in forms of side products like hydrogen chloride or chloride salts. , Thus, sustainable chlorine recycling becomes crucial for clean production in the chemical industry. To recycle chlorine from HCl, quite a few electrochemical processes has been developed. For example, the reaction kinetics were well established for deep understanding of catalytic oxidation of HCl , ; a phase change absorbent (MDEA/NHD) was developed for HCl absorption to produce hydrogen and chlorine by electrolysis . However, as the generation of HCl is unavoidable in traditional chlorination processes, the recycling system requires intensive energy input and results in great emissions …”
Section: Introductionmentioning
confidence: 99%
“…To recycle chlorine from HCl, quite a few electrochemical processes has been developed. 4−7 For example, the reaction kinetics were well established for deep understanding of catalytic oxidation of HCl 8,9 ; a phase change absorbent (MDEA/NHD) was developed for HCl absorption to produce hydrogen and chlorine by electrolysis. 10 However, as the generation of HCl is unavoidable in traditional chlorination processes, the recycling system requires intensive energy input and results in great emissions.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In the course of these chlorine-related processes, the utilization ratio of chlorine atoms is less than a half, resulting in a large amount of hydrogen chloride (HCl) emission as byproduct. 3,4 Therefore, converting HCl to Cl 2 to construct a closed circulation of chlorine resource became an inevitable choice to ensure the sustainable development of chlorine-related industries. 5,6 Compared with electrolysis and direct oxidation, the catalytic oxidation of HCl to Cl 2 (Deacon process) has been considered to be the most economical route, and the RuO 2 -based catalyst supported on TiO 2 (rutile) or SnO 2 (cassiterite) was one of the current commercialized catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Chlorine (Cl 2 ) is one of the important chemical feedstock widely used in the production of polymers, crop protection, pharmaceuticals, organic fluorine, and others. , In the course of these chlorine-related processes, the utilization ratio of chlorine atoms is less than a half, resulting in a large amount of hydrogen chloride (HCl) emission as byproduct. , Therefore, converting HCl to Cl 2 to construct a closed circulation of chlorine resource became an inevitable choice to ensure the sustainable development of chlorine-related industries. , Compared with electrolysis and direct oxidation, the catalytic oxidation of HCl to Cl 2 (Deacon process) has been considered to be the most economical route, and the RuO 2 -based catalyst supported on TiO 2 (rutile) or SnO 2 (cassiterite) was one of the current commercialized catalysts. , The contrast of the effect of support type (TiO 2 , SnO 2 , SiO 2 , Al 2 O 3 , etc.) on the performance of RuO 2 -based catalysts has been previously investigated by researchers.…”
Section: Introductionmentioning
confidence: 99%